Liquid scintillation counting at the limit of detection in biogeosciences - Schubert, Florian; Kallmeyer, Jens (Frontiers in Microbiology, 2023)
LLiquid scintillation is widely used to quantify the activity of radioisotopes. We present an overview of the technique and its application to biogeosciences, particularly for turnover rate measurements. Microbial communities and their metabolism are notoriously difficult to analyze in low energy environments as biomass is exceedingly sparse and turnover rates low. Highly sensitive methods, such as liquid scintillation counting, are required to investigate low metabolic rates and conclusively differentiate them from the background noise of the respective analyzer. We conducted a series of experiments to explore the effects of luminescence, measurement time and temperature on scintillation measurements. Luminescence, the spontaneous emission of photons, disproportionally affects samples within the first few hours after sample preparation and can be minimized by following simple guidelines. Measurement time will negatively affect liquid scintillation analysis if the time window is too short or if the effect of background noise makes up a significant proportion of the sample. Measurement temperature affected liquid scintillation analysis only when the temperature during the measurement reached approximately 30°C or higher, i.e. the liquid scintillation analyzer was placed in an environment without temperature control, but not when heat control was applied or chemicals were stored at elevated temperatures. Basic understanding on the functionality of a liquid scintillation analyzer and simple precaution prior to the measurement can significantly improve the background and therefore allow for determination of low turnover rates previously lost in the background noise.